Unexpected Facile Synthesis of Tetronic Acid During the Research on Stereospecific Total Synthesis of (+)-Biotin Starting from D-Erythorbic Acid as Chiral Pool - Li, Xiao-Kang; Xiong, Fei; Shen, Zhong-Yuan; Zhang, Shu-Ping; Zhou, Yi-Hao; Xu, Ming-Lu; Zhou, Zi-Qian (Asian Journal of Chemistry, 2015)
The reaction of D-erythronolactone (8) with the methanesulfonyl chloride in the presence of triethylamine afforded, after unexpected elimination reaction, the tetronic acid is obtained in excellent yield and chemical purity, instead of the dimesylates (7).